2018
DOI: 10.22270/ujpr.v3i3.165
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Susceptibility Pattern and Risk Factors of Mrsa Isolated From Clinical Specimens Among Military Patients at 48 Medical Compound in Sana'a City-Yemen

Abstract: Methicillin-resistant strains of S. aureus evolved in the 1970 and have troubled hospitals worldwide with persistent infections in patients. The objectives of this study were to determine the prevalence, antimicrobial susceptibility pattern and risk factors of MRSA isolated from clinical specimens among military patients at 48 Medical Compound in Sana'a city -Yemen. The study included 233 patients of whom suffering from Staphylococcus aureus infections. Specimens and data collected from November 2016 to Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…if CoNS was isolated from the skin or soft tissue bacterial culture of a suspected infectious lesion, the isolated organism should be suggested as the pathogen and appropriate treatment should be started [43][44][45] . Among the antibiotics tested differently, the results of current study showed that the rate of resistance to linezolid was very low (0.42%) (Table 3) making it highly efficient antibiotics against Enterococcus spp and S. aureus which it was in accord with the rates previously described by Al-Safani et al, 20 32 . Overall, the results of the current study showed that sulfamethoxazole/trimethoprim, ceftazidime, ampicillin, ceftorexime and cefotaxime are ineffective antibiotics against GPB or GNB.…”
Section: Table 3: Antibiotics Susceptibility Profile Of Isolated Bacteriasupporting
confidence: 87%
See 2 more Smart Citations
“…if CoNS was isolated from the skin or soft tissue bacterial culture of a suspected infectious lesion, the isolated organism should be suggested as the pathogen and appropriate treatment should be started [43][44][45] . Among the antibiotics tested differently, the results of current study showed that the rate of resistance to linezolid was very low (0.42%) (Table 3) making it highly efficient antibiotics against Enterococcus spp and S. aureus which it was in accord with the rates previously described by Al-Safani et al, 20 32 . Overall, the results of the current study showed that sulfamethoxazole/trimethoprim, ceftazidime, ampicillin, ceftorexime and cefotaxime are ineffective antibiotics against GPB or GNB.…”
Section: Table 3: Antibiotics Susceptibility Profile Of Isolated Bacteriasupporting
confidence: 87%
“…According to estimates by the World Health Organization (WHO) and United Nations report, deaths due to antimicrobial resistance could increase with the time 4, 5 . Nowadays, antimicrobial resistance (AMR) is a major public health threat, 6,7 and antimicrobial resistance bacteria in different hospital departments are increasing dramatically all over the world and in Yemen this problem is more extensive and complex [8][9][10][11][12][13][14][15][16][17][18][19][20] . As for some details of the previous work in Yemen, these studies mostly focused on studying the sensitivity to antibiotics for each bacteria separately 8-20 , while the current study studied the resistance to all bacterial isolates, and the current study also identified the temporal correlation of the rate of increase in the prevalence of resistance of bacterial isolates to the antibiotics used in the study area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many bacterial diseases occur in hospitals and in community due to MRSA strains and sometimes lead to death 10-12 . S. aureus infection, including MRSA strains, has long been common in Yemen 13 . Because the arbitrary use of antibiotics is a typical practice, hospital environments are not clean enough and crowding of patients and health workers supports the spread of infectious germs including S. aureus 13 .…”
Section: Introductionmentioning
confidence: 99%
“…An example of the importance of this topic in Sana'a and the situation where this information is useful in Sana'a as well. As the rates of antibiotic resistance are high, doctors depend on giving antibiotics experimentally without bacterial isolation and sensitivity testing to antibiotics [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . Treatment for UTIs often begins with an experiment.…”
Section: Introductionmentioning
confidence: 99%